Dislocation Structures in Low-Angle Grain Boundaries of α-Al2O3 - Eita Tochigi; Atsutomo Nakamura; Naoya Shibata; Yuichi Ikuhara (Crystals, 2018)
Alumina (α-Al2O3) is one of the representative high-temperature structural materials. Dislocations in alumina play an important role in its plastic deformation, and they have attracted much attention for many years. However, little is known about their core atomic structures, with a few exceptions, because of lack of experimental observations at the atomic level. Low-angle grain boundaries are known to consist of an array of dislocations, and they are useful to compose dislocation structures. So far, we have systematically fabricated several types of alumina bicrystals with a low-angle grain boundary and characterized the dislocation structures by transmission electron microscopy (TEM). Here, we review the dislocation structures in { 11 2 ¯ 0 } / [ 0001 ] , { 11 2 ¯ 0 } / 〈 1 1 ¯ 00 〉 , { 1 1 ¯ 00 } / 〈 11 2 ¯ 0 〉 , ( 0001 ) / 〈 1 1 ¯ 00 〉 , { 1 ¯ 104 } / 〈 11 2 ¯ 0 〉 , and ( 0001 ) / [ 0001 ] low-angle grain boundaries of alumina. Our observations revealed the core atomic structures of b = 1 / 3 〈 11 2 ¯ 0 〉 edge and screw dislocations, 〈 1 1 ¯ 00 〉 edge dislocation, and 1 / 3 〈 1 ¯ 101 〉 edge and mixed dislocations. Moreover, the stacking faults on { 11 2 ¯ 0 } , { 1 1 ¯ 00 } , and ( 0001 ) planes formed due to the dissociation reaction of the dislocations are discussed, focusing on their atomic structure and formation energy.